Transforming governance and institutions for global sustainability: Key insights from the Earth System Governance Project - Frank Biermann (2018)
The current institutional framework for sustainable development is by far not strong enough to bring about the swift transformative progress that is needed. This article contends that incrementalism-the main approach since the 1972 Stockholm Conference-will not suffice to bring about societal change at the level and speed needed to mitigate and adapt to earth system transformation. Instead, the article argues that transformative structural change in global governance is needed, and that the 2012 United Nations Conference on Sustainable Development in Rio de Janeiro must turn into a major stepping stone for a much stronger institutional framework for sustainable development. The article details core areas where urgent action is required. The article is based on an extensive social science assessment conducted by 32 members of the lead faculty, scientific steering committee, and other affiliates of the Earth System Governance Project. This Project is a ten-year research initiative under the auspices of the International Human Dimensions Programme on Global Environmental Change (IHDP), which is sponsored by the International Council for Science (ICSU), the International Social Science Council (ISSC), and the United Nations University (UNU). © 2012.